Robotics Education_Emerging Trend in Technology Education - Miskon, Muhammad Fahmi (Malaysia Board of Technologists (MBOT), 2017)
The Institute of Electrical and Electronics Engineers (IEEE) Robotics and Automation Society (RAS) Malaysia is a non-profit organization dedicated to advancing technology for humanity. It focuses on innovation, education, and fundamental and applied research in robotics and automation. Robotics research emphasizes intelligence and adaptability, while automation research focuses on efficiency, productivity, quality, and reliability. The society promotes close cooperation and exchange of technical information among its members and affiliates through meetings, sponsorships, and support for robotic and innovative competitions. The use of robots in education is highly encouraged, with the PRIDE competition being a regular track in RAS Malaysia conferences. The competition, endorsed by the Ministry of Science, Technology and Innovation Malaysia and Ministry of Education Malaysia, attracts participation from primary and secondary schools, colleges, universities, and private robotic clubs. Robotic courses in institutes of higher learnings (IHLs) prepare graduates for robotics-related jobs and expose students to skills required in the future, such as computational and critical thinking, complex problem-solving, and creativity.